Commenters reading position toward the news of dissolution of Islamic Defenders Front in Facebook - Ahmadi F. , Yusep (Proceder: Applied Linguistics, Literature, and Language Education, 2023)
The news about the dissolution of the Islamic Defenders Front (FPI) attracted public attention. This is due to the action of FPI as a mass organization in Indonesia often make pros and cons. The various actions are regarded humanist by some people but the others claim that the actions were harsh and radical. Thus, the government dissolved FPI. The purpose of this study is to describe commenters reading position toward the news of the dissolution of FPI by the government in online media JEO.kompas.com which was spread on Facebook. The data sources of this research are taken from 34 comments from a news about the dissolution of FPI which was spread on Facebook. This research uses descriptive qualitative research. Data were collected by using documentation. Data were analyzed by using functional approach, pragmatics, and Stuart Hall’s theory about the position of the audience in constructing messages. The results showed that there are lingual markers such as modality, transitivity and lexicalization which show the position of reading the news. There are 23 comments in the dominant hegemonic position, 7 comments in negotiation position and 4 comments in oppositional position. Based on these findings it can be concluded that 68% of readers in online media JEO.kompas.com which was spread on Facebook accepted and supported the dissolution of Islamic Defenders Fronts.